Dari Kemudahan ke Kepuasan: Peran Perceived enjoyment dalam Mendorong Impulse buying pada Pengguna Aplikasi Shopee - Annisa Rahmadani; Fitria Ridhaningsih (Jurnal Informatika Ekonomi Bisnis, 2025)
The advancement of digital technology has significantly transformed consumer shopping behavior, particularly through e-commerce platforms such as Shopee. Factors such as Perceived Ease of Use, Price discount strategies, and the enjoyment experienced during shopping are believed to influence consumers’ tendency to engage in impulse buying. This study aims to examine the influence of Perceived Ease of Use and Price discount on Impulse buying among Shopee users in Padang City, as well as to investigate the mediating role of perceived enjoyment. A quantitative research approach was employed, utilizing a survey method with purposive sampling. The sample consisted of 150 active Shopee users in Padang who had previously made impulsive purchases. Data were collected through an online questionnaire using a Likert scale and analyzed using Structural Equation Modeling with Partial Least Squares. The findings indicate that Perceived Ease of Use does not have a significant effect on impulse buying. However, Perceived Ease of Use has a positive and significant effect on perceived enjoyment. Furthermore, perceived enjoyment positively and significantly influences impulse buying. Price discount also shows a positive and significant effect on both impulse buying and perceived enjoyment. In addition, Perceived Ease of Use has a positive and significant indirect effect on impulse buying through perceived enjoyment, and price discount similarly exerts a positive and significant indirect effect on impulse buying through perceived enjoyment. Overall, these results highlight the essential role of emotional experience in driving impulsive purchasing behavior on e-commerce platforms.